Promoting Socio-scientific Issues-based Learning in Biology: Indonesian Students’ and Teacher’s Perceptions and Students’ Informal Reasoning - Subiantoro, Agung Wijaya (Curtin University, 2017)
This case study-based research was designed to investigate Indonesian biology teachers’ and students’ perceptions and students’ informal reasoning of SSI-based lessons. Data were collected through questionnaires, interviews, observations and informal reasoning activity sheets. Research revealed that SSI-based lessons are perceived as a new experience by both teachers and students with students’ informal reasoning demonstrating multi-dimensional aspects. Furthermore, the essential aspects regarding teachers’ and students’ perceptions and reasoning are discussed in this research.